Modelling S-Wave Velocity Structure Beneath the Central Main Ethiopian Rift Using Receiver Functions - Kibret, Birhanu A.; Ayele, Atalay; Keir, Derek (Frontiers in Earth Science, 2022)
We applied the receiver function technique on high-quality teleseismic earthquake data recorded by the RiftVolc broadband network from February 2016 to October 2017. The receiver functions are inverted to estimate the shear wave (S-wave) velocity (Vs) structure beneath the lower crust and uppermost mantle in the Central Main Ethiopian Rift and the Eastern Plateau. The observed low Vs (~2-3 km/s) uppermost crust (<6 km depth) is interpreted as sedimentary and/or volcanic layers. Beneath the rift valley, crustal Vs is heterogeneous laterally and with depth. In particular, slow Vs is localised beneath volcanic centres in the upper-mid crust but ubiquitously slow in the lower crust. The Vs of ~3.5 km/s in combination with apriori constraints of Vp of ~6.8 km/s are most consistent with a model of <4% partial melt. In addition, the velocity contrast is small between the lower crust and upper mantle. The results suggest that partial melt in the lower crust beneath magmatically active rifts might be more widespread than previously thought, and an important component of the magma plumbing system. In contrast, Vs is far more homogeneous and faster beneath the Eastern Plateau, with a distinct and sharp velocity contrast observed between the crust and upper mantle at Moho, jointly suggestive of very little crustal modification from magmatism.